2015
DOI: 10.1109/twc.2015.2443044
|View full text |Cite
|
Sign up to set email alerts
|

Joint Precoding and Load Balancing Optimization for Energy-Efficient Heterogeneous Networks

Abstract: Abstract-This paper considers a downlink heterogeneous network, where different types of multiantenna base stations (BSs) communicate with a number of single-antenna users. Multiple BSs can serve the users by spatial multiflow transmission techniques. Assuming imperfect channel state information at both BSs and users, the precoding, load balancing, and BS operation mode are jointly optimized for improving the network energy efficiency. We minimize the weighted total power consumption while satisfying quality-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Because 80% of the power in current networks is consumed at the BSs [11], the BS technology needs to be redesigned to reduce the power consumption as the wireless traffic grows. Many researchers have investigated how the physical layer transmissions can be optimized to reduce the transmit power, while maintaining the quality-of-service (QoS); see [11]- [16] and references therein. In particular, the precoding vectors and power allocation were jointly optimized in [12] under perfect channel state information (CSI).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because 80% of the power in current networks is consumed at the BSs [11], the BS technology needs to be redesigned to reduce the power consumption as the wireless traffic grows. Many researchers have investigated how the physical layer transmissions can be optimized to reduce the transmit power, while maintaining the quality-of-service (QoS); see [11]- [16] and references therein. In particular, the precoding vectors and power allocation were jointly optimized in [12] under perfect channel state information (CSI).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, [14] showed that most joint power allocation and BS-user association problems with power constraints are NP-hard. The recent papers [15], [16] consider a relaxed problem formulation where each user can be associated with multiple BSs and show that these problems can be solved by convex optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, optimizing EE performance for downlink transmission in HetNets has attracted a lot of research interest recently and mixed deployment of HetNets has been shown to have a higher EE. To save the HetNets energy, some actice/sleep regimes for conventional HetNets and massive MIMO HetNets were proposed in [3,4,28,51]. It is importantly noted that the maximizing EE performance does not try to minimize the beamformer power since EE merit is a ratio of the network sum-rate and the total power consumption.…”
Section: Energy Efficiency In Small Cell With User Associationmentioning
confidence: 99%
“…Without the fronthaul capacity constraint (9c), the optimal solution can be efficiently obtained [16], [17]. For (14), a brute force approach can be applied to achieve the optimal power adaptation.…”
Section: Low-complexity Algorithmmentioning
confidence: 99%